Mānuka Clones Differ in Their Volatile Profiles: Potential Implications for Plant Defence, Pollinator Attraction and Bee Products - Effah E; Min Tun K; Rangiwananga N; McCormick AC (MDPI (Basel, Switzerland), 2022)
The New Zealand native plant mānuka (Leptospermum scoparium) is representative of the country’s North and South Islands flora. This species is essential to the growing community of honey producers due to its honey’s antimicrobial and antioxidant properties, attributed to the presence of methylglyoxal (MGO), derived from dihydroxyacetone (DHA) in the nectar. Several clones and cultivars have been selected to optimize DHA production. Still, nothing is known about the volatile emissions of these artificially selected plants. Volatile organic compounds (VOCs) can influence their interactions with the environment, such as pollinator foraging decisions, which may subsequently affect the plants’ products. This study explored the aboveground volatile organic compounds (VOCs) emitted by eight different mānuka genotypes (six clones and two wild cultivars) under field conditions during the spring season. Volatiles were collected using the “push–pull” headspace sampling technique and analyzed using gas chromatography-mass spectrometry (GC-MS). Our results show that mānuka plants emit large amounts of terpenoids, with sesquiterpenes and monoterpenoids being the most abundant groups of compounds. The results also show variation in the total green leaf volatiles, total sesquiterpenes, and specific compounds between genotypes and suggest that artificially selected plants have a significant variation in their chemical profiles. The potential impacts of these results on the plant’s defence, pollinator attraction and bee products are discussed.
Keywords: plant genotype; plant secondary metabolites; artificial selection; plant volatiles; green leaf volatiles; terpenoids; honey; propolis